Experimental Study of Pneumatic Two-Stage Small-Size Radial Turbine - Pavlovich Kuznetsov, Yuri; Anatolevich Zakharov, Lev; Nikolaevich Khrunkov, Sergey; Aleksandrovich Kraynov, Artem; Evgenevich Zhukov, Aleksandr (International Journal of Engineering and Technology, 2018)
This work is aimed at experimental study of the influence of design variables of the first jet reaction stage on the properties of pneumatic two-stage small-size radial turbine. Kinematic layout of the considered turbine is presented, operating processes are described, the final target is formulated to reveal the influence of certain geometrical parameters of the first jet reaction stage which determine overall turbine efficiency. Criterion of nozzle efficiency is determined, variable parameters of multifactorial experiment are selected; experimental facility and procedure of data processing are described. The main experimental results are presented. It is established that the greatest influence on the turbine efficiency is exerted by supersonic nozzle expansion angle. Optimum combination of geometrical expansion extent and geometrical expansion angle of supersonic nozzle of the first jet reaction stage of two-stage small-size radial turbine has been experimentally determined.Â Â